Meta-analysis of Acupuncture Intervening Benign Prostatic Hyperplasia - Yang, Xueyuan; Cai, Wanling; Yu, Wenjuan; Zhou, Fang (Chinese medicine and natural products, 2025)
This study aimed to evaluate the effectiveness of acupuncture for benign prostatic hyperplasia (BPH).We searched PubMed, EMBASE, Cochrane Library, Chinese Biomedical Literature Database, Chinese National Knowledge Infrastructure, Wanfang Data, and China Science and Technology Journal Database from their inceptions to February 1, 2022. The language was restricted to English and Chinese. Two researchers independently screened the literature, extracted data, and evaluated the risk bias of the included study according to the Cochrane Handbook 5.1.0. A meta-analysis was performed using Review Manager version 5.3.Twenty-two studies with 1,765 participants were selected to be incorporated in the meta-analysis. The experimental groups (EGs) showed greater benefit on therapeutic effects (relative risk [RR]: 1.23, 95% CI: 1.16, 1.3; P < 0.00001), International Prostate Score Scale (mean difference [MD]: −2.06, 95% CI: −3.17, −0.96; P = 0.0002), maximum urinary flow rate (MD: 1.7, 95% CI: 0.89, 2.52; P < 0.0001), postvoid residual urine volume (MD: −8.25, 95% CI: −12.14, −4.36; P < 0.0001), quality of life (MD: −0.55, 95% CI: −0.8, −0.29; p < 0.0001) compared with the control groups, whereas for prostate volume (MD: −0.87, 95% CI: −2.66, 0.92; P = 0.34) was not significantly improved in the EGs. Nevertheless, no statistical variation in the reduction of adverse reactions was observed.Acupuncture therapy, a wildly applied complementary–alternative treatment, may help in the management of BPH.
Keywords: benign prostatic hyperplasia; acupuncture; meta-analysis; systematic review